Hallazgo de restos de la serpiente Dinilysia patagonica Smith-Woodward 1901 en una nueva localidad del Santoniano de Patagonia, Argentina - Triviño, Laura Natalia (2015)
In this study, we describe new remains of the cretaceous snake Dinilysia patagonica from beds of the locality Barreales Norte, Bajo de la Carpa Formation (Upper Santonian), Neuquén province, Argentina. The material comprises the back of a partially preserved skull, articulated with a fragment of the compound bone, atlas and axis. Additionally, six fragments of precloacal vertebrae have been preserved. The assignation to Dinilysia patagonica is based on: large skull, otooccipital with long paraoccipital process adjacent to an elongate supratemporal that extends farther the level of the occipital condyle; well developed sagital crest of parietal bone, continuously joined with the supraoccipital crest; italics I-like prootic; wide, short and robust vertebrae; prezygapophyses long and highly inclined above the horizontal; triangular section of vertebral centrum; reduced prezygapophyseal process; flattened neural arches with straight posterior edge. This material adds a new Upper Cretaceous location for the distribution of the species at the north of the Neuquén River.